Modelación de erosión hídrica en los cantones de Sozoranga, Puyango y Paltas, mediante sistemas de información geográfica - Ruiz Bermeo, Nixon Bladimir (2017)
Water erosion is one of the main problems caused by soil degradation. The RUSLE model was applied in the cantons of Sozoranga, Puyango and Paltas, in order to identify the areas most susceptible to water erosion. Its application was made using Geographic Information Systems (GIS) that are a useful tool in the estimations. In the RUSLE calculation, information was generated, with field outputs to the study sites and also the use of secondary information. Meteorological station information was used, soil erodibility was determined; Determining the structure, permeability, texture, very fine sand and organic matter, vegetation cover, topography, and management practices. With the results obtained, erosion control alternatives were proposed in the most affected areas. The results revealed that the current water erosion in the Sozoranga canton between high and very high goes from 9.60 to 7.90%, in the Puyango canton between high and very high are 16.50 to 10.50% and finally in The Canton Paltas 19.30 to 5.30%. As these cantons are productive in different agricultural activities, they tend to perform poor soil conservation practices, which in the event of heavy precipitation, and the lack of vegetation cover generates greater loss of soil. Conservation practices such as reforestation, agroforestry systems, contour crops, which were modeled, presented a reduction of soil water erosion, for the Sozoranga canton of 5.40 to 6.40% between high and very high, in the Puyango canton between high and very high goes from 2.80 to 6.80% and finally in the Paltas canton with 8.14 to 4.60%.